2015
DOI: 10.1586/14737167.2016.1102062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, and burden of major depressive disorder in urban China

Abstract: MDD in urban China may be under-diagnosed and undertreated. Awareness and better access to treatments may help alleviate the burden of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
5
31
0
Order By: Relevance
“…The prevalence of MDD between different regions in China varied from 1% to 6.5% [1921]. MDD prevalence in urban China was 6.0% with a relatively low diagnosed rate (8.3%) and only 51.5% currently used prescription medication for depression [22]. Our study reported that the prevalence of depressive symptom was 5.9% in rural Northeast China which seemed to be close to the urban areas [23].…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of MDD between different regions in China varied from 1% to 6.5% [1921]. MDD prevalence in urban China was 6.0% with a relatively low diagnosed rate (8.3%) and only 51.5% currently used prescription medication for depression [22]. Our study reported that the prevalence of depressive symptom was 5.9% in rural Northeast China which seemed to be close to the urban areas [23].…”
Section: Discussionmentioning
confidence: 86%
“…As a productivity outcome, previous reports have identified impairments in the ability of depressed patients to perform nonwork-related routine day-to-day activities (or activity impairment) 20,21. Antidepressant treatment results in reduced activity impairment 22.…”
Section: Introductionmentioning
confidence: 99%
“…162 Based on the 2012 China National Health and Wellness Survey, the prevalence of mental health disorders was 6% in urban areas. 163 Highly populated cities along the eastern coast (such as Shenyang and Shanghai) and cities in west China that have high population densities had poorer depression scale scores than did other cities. 164 The prevalence of mental health problems is high among migrant workers.…”
Section: Mental Disorders Statusmentioning
confidence: 97%
“…People with such disorders reported lower health-related quality of life scores and had lower productivity and resource utilisation. 163…”
Section: Mental Disorders Statusmentioning
confidence: 99%